(untitled) (Research, Society and Development, 2025)
Plumeria pudica produces a protein-rich latex (PLPp) with anti-inflammatory, antinociceptive and antidiarrheal properties, in addition to reducing periodontitis and acting as a protector in ulcerative colitis. The present study aimed to evaluate the effects of latex proteins on intestinal mucositis induced by 5-fluorouracil, in order to contribute with significant information for the solution of this problem and, if possible, become a therapeutic tool for intestinal mucositis. For this purpose, female Balb/c mice were divided into three groups: saline, 5-FU and PLPp + 5-FU. Mucositis was induced with three doses of 5-FU, while PLPp was administered one hour before each chemotherapy application, for three days. The small intestine was collected for histopathological, morphometric, oxidative stress (MDA, GSH and SOD) and inflammatory (MPO and NO3/NO2) analyses. The in vitro cytotoxicity of PLPp was evaluated alone and in combination with 5-FU. PLPp reduced MPO and NO3/NO2 levels, demonstrating an anti-inflammatory action, although it did not reverse the histopathological alterations. Furthermore, PLPp did not show cytotoxicity in the HCT 116 cells tested, and its association with 5-FU did not reduce the IC50 of the chemotherapy drug. It was concluded that PLPp protects the intestinal mucosa against oxidative stress and inflammation induced by 5-FU, although its proteolytic activity may compromise the pharmacological efficacy.